Trade unions and multinational companies: A multi-level challenge - Paul Marginson (University of Warwick, Industrial Relations Research Unit, 2016)
Trade unions face major challenges in developing effective responses to the growing international scope, integration and complexity of multinational companies' operations. There is marked variation in trade unions' responses, which may be local and national or cross-border in nature. Focusing on cross-border union co-operation and action, the paper shows that considerations of both structural and institutional contingency and union agency are important in accounting for the marked variation in union responses. In examining contingency, the paper highlights how a series of institutional and structural factors, relating to the national and regional institutional environments in which MNCs are based, and where they locate their operations; sector of operation; and the business structure and strategy of MNCs, tend to shape the nature of union responses. By exploring the role of agency from two perspectives - bottom up and top down - the multi-level nature of the challenge confronting unions in establishing viable forms of transnational cooperation and action is demonstrated. A perceptible shift is underway towards contexts in which local or national responses are no longer adequate or appropriate, and towards those which call for cross-border initiatives.
Keywords: 330; Gewerkschaft; Internationale Arbeitsbeziehungen; Multinationales Unternehmen; Institutionelle Infrastruktur